Optimizing current strategies and applications in industrial engineering - Sahoo, Prasanta (Engineering Science Reference, 2019)
"This book examines applied and theoretical aspects of industrial engineering and related areas. It also explores empirical and theoretical research on the development, improvement, implementation, and evaluation of integrated systems in engineering"--